2018
DOI: 10.1080/15548627.2018.1466013
|View full text |Cite
|
Sign up to set email alerts
|

Role of the MAPK/cJun NH 2 -terminal kinase signaling pathway in starvation-induced autophagy

Abstract: Autophagy is required for cellular homeostasis and can determine cell viability in response to stress. It is established that MTOR is a master regulator of starvation-induced macroautophagy/autophagy, but recent studies have also implicated an essential role for the MAPK8/cJun NH2-terminal kinase 1 signal transduction pathway. We found that MAPK8/JNK1 and MAPK9/JNK2 were not required for autophagy caused by starvation or MTOR inhibition in murine fibroblasts and epithelial cells. These data demonstrate that MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The serum contains significant IGF-1 levels [ 23 ], and therefore, we cultured cells with/without IGF-1 in a serum-starved media. Since serum starvation is a potent autophagy/mitophagy inducer [ 24 , 25 ], IGF-1 effects were tested in cells with basal enhancement in autophagy. This approach increased sensitivity of autophagy detection in experiments with “aged” cells with relatively low autophagy/mitophagy levels.…”
Section: Resultsmentioning
confidence: 99%
“…The serum contains significant IGF-1 levels [ 23 ], and therefore, we cultured cells with/without IGF-1 in a serum-starved media. Since serum starvation is a potent autophagy/mitophagy inducer [ 24 , 25 ], IGF-1 effects were tested in cells with basal enhancement in autophagy. This approach increased sensitivity of autophagy detection in experiments with “aged” cells with relatively low autophagy/mitophagy levels.…”
Section: Resultsmentioning
confidence: 99%
“…50 The role of the complex MAPK signaling pathway in the regulation of autophagy is context-dependent and has not yet been fully described. 51 Elucidation of the signaling cascades that regulate autophagy and its mechanisms will therefore be highly beneficial to disease treatment and prevention.…”
Section: Axl Signaling Is Associated With a Novel Gene Signature Of Pmentioning
confidence: 99%
“…According to a previous study, autophagy may alter the activity of MAPKs, including JNK, ERK1/2 and p38, and affect cell proliferation, survival and apoptosis under various conditions. 16 Therefore, to further verify whether autophagy prevents P. aeruginosa -induced RAW264.7 cell apoptosis by MAPK pathway, we detected p-JNK, p-ERK1/2 and p-p38 protein expression of RAW264.7 cells treated with rapamycin for 2 h or 3-MA for 6 h and then exposed to P. aeruginosa for 4 h. The results showed that rapamycin potently suppressed the activation of p-JNK, p-ERK1/2 and p-p38 production in RAW264.7 cells infected with P. aeruginosa ( Figure 5c ). However, 3-MA promoted the activation of p-JNK and p-p38 (Figure S3).…”
Section: Resultsmentioning
confidence: 99%